Gender Performativity in Wind Breaker Anime and Indonesian Audience Response - Fanani, Ahmad Farid; Rifat Syauqi Efendi; Fiko Savero; Teguh Iswahyudi (Yinyang: Jurnal Studi Islam Gender dan Anak, 2026)
In societies where social norms are still largely based on traditional gender dichotomies, non-conventional gender expressions frequently encounter rejection and stigmatization, a phenomenon observed in both real life and popular media, including anime. This study employs Roland Barthes' semiotic approach to analyze Tsubaki's character in the anime Wind Breaker, aiming to uncover the denotative and connotative meanings of the gender symbols displayed. By focusing on visual elements such as lipstick, feminine clothing, gestures, and dialogue, the research investigates how these signs construct a narrative about gender identity that is fluid and performativity. Findings reveal that Tsubaki's representation acts as a form of counter-hegemonic discourse, challenging binary gender schemes and fostering a more inclusive interpretation of identity. However, the Indonesian audience's non-acceptance of non-conventional gender expressions in Wind Breaker indicates resistance to content perceived as deviating from local values. This research not only underscores anime's potential as a medium for social critique but also promotes discussion on the crucial need for more diverse and humane gender representation in the global media landscape.